2019
DOI: 10.3389/fmicb.2019.02456
|View full text |Cite
|
Sign up to set email alerts
|

Mangrove-Associated Fungal Communities Are Differentiated by Geographic Location and Host Structure

Abstract: Marine fungi on the whole remain understudied, especially in the highly diverse Southeast Asian region. We investigated the fungal communities associated with the mangrove tree Avicennia alba throughout Singapore and Peninsular Malaysia. At each sampling location, we examined ten individual trees, collecting leaves, fruits, pneumatophores, and an adjacent sediment sample from each plant. Amplicon sequencing of the fungal internal transcribed spacer 1 and subsequent analyses reveal significant differences in fu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
30
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 49 publications
(35 citation statements)
references
References 79 publications
5
30
0
Order By: Relevance
“…Shannon diversity values are comparable among all locations when all organs and sediment are combined, and fungal community diversity in the leaves, fruits and pneumatophores is comparable, while sediment samples are approximately twice as diverse as all other samples. This is consistent with previous work showing that soils are highly diverse reservoirs of fungal biodiversity, containing hundreds of thousands of fungal species (Bridge and Spooner 2001 ; Lee et al 2019a ). Likewise we find the highest number of fungal ASVs in the sediment samples.…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…Shannon diversity values are comparable among all locations when all organs and sediment are combined, and fungal community diversity in the leaves, fruits and pneumatophores is comparable, while sediment samples are approximately twice as diverse as all other samples. This is consistent with previous work showing that soils are highly diverse reservoirs of fungal biodiversity, containing hundreds of thousands of fungal species (Bridge and Spooner 2001 ; Lee et al 2019a ). Likewise we find the highest number of fungal ASVs in the sediment samples.…”
Section: Discussionsupporting
confidence: 93%
“…As in Tisthammer et al ( 2016 ), and also shown for another mangrove Avicenna alba recently (Lee et al 2019a ), we suggest that the fungal community distribution is strongly shaped by the environment, a consequence of differences in habitat type throughout Peninsular Malaysia and Singapore. Further supporting this idea, the coasts of Malay Peninsula are split in two by the Titiwangsa Mountain range, which forms the backbone of the peninsula with its > 2000-m maximum elevation.…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…Like other studies examining microbial diversity and coral-associated bacteria throughout Singapore and the region, we show significant differences in microbial community structure among sampling locations 10,24,39,40 . All samples are generally dominated by Proteobacteria and Cyanobacteria, and samples collected from Tanah Merah appear most distinct in comparison to other sites.…”
Section: Discussionsupporting
confidence: 71%